2022
DOI: 10.1158/1078-0432.ccr-22-1898
|View full text |Cite
|
Sign up to set email alerts
|

Interactions in CSF1-Driven Tenosynovial Giant Cell Tumors

Abstract: Purpose: A major component of cells in Tenosynovial Giant Cell Tumor (TGCT) consists of bystander macrophages responding to CSF1 that is overproduced by a small number of neoplastic cells with a chromosomal translocation involving the CSF1 gene. An autocrine loop was postulated where the neoplastic cells would be stimulated through CSF1R expressed on their surface. Here we use single cell RNA sequencing to investigate cellular interactions in TGCT. Experimental Design: A total of 18,788 single cells from three… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…There is increasing evidence that shows the regulatory element or membrane domain loss by losing various proportions of the 3′ end of CSF1 and new research indicates that the self‐sustaining autocrine CSF1‐CSF1R signaling loop in neoplastic cells is lacking based on single‐cell sequencing. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is increasing evidence that shows the regulatory element or membrane domain loss by losing various proportions of the 3′ end of CSF1 and new research indicates that the self‐sustaining autocrine CSF1‐CSF1R signaling loop in neoplastic cells is lacking based on single‐cell sequencing. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 6 The clonal population expresses high levels of colony‐stimulating factor 1 (CSF1), which leads to the recruitment of non‐neoplastic cells expressing the CSF1 receptor (CSF1R). This is referred to as the “landscape effect.” 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Tendon sheath giant cell tumor (TGCT) is a benign tumor that primarily grows within joints and bursae, or extends along the tendon sheath ( 1 ). This type of tumor originates from synovial cells or mesenchymal cells differentiated into synovial cells ( 1 ). TGCT can be classified into two types: localized and diffuse ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have combined them to construct a prognosis model [ 10 ] and show the landscape of the immune microenvironment [ 11 ] and the mechanisms of biological processes [ 12 ]. Using sequencing techniques, researchers revealed that osteoclastogenesis and osteoclast differentiation are vital characteristics of TGCT [ 13 , 14 ]. However, no studies explore the possibility of diagnosing TGCT using osteoclast-specific genes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we integrated two scRNA-seq datasets [ 14 , 15 ] and two microarray datasets [ 13 , 16 ] from Gene Expression Omnibus (GEO) dataset to identify osteoclast-specific up-regulated genes (OCSURGs) to predict the diagnosis of TGCT. Up-regulated genes were screened from the discovering cohort (GSE3698, GSE210750, and GSE152805).…”
Section: Introductionmentioning
confidence: 99%